AB0304 Clinical and serological response to tocilizumab in patients with rheumatoid arthritis. (23rd January 2014) - Casu, C.; Bruschi, E.; Alpini, C.; Marceglia, S.; Giacomelli, L.; Epis, O.
Abstract : Background: The role of rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies (anti-CCP) in the response to treatment for rheumatoid arthritis (RA) is not fully understood. Studies investigating changes in the levels of RF in response to synthetic and biological DMARDs have not been able to confirm a definitive relationship between decreased RF subtypes and clinical response, while studies investigating changes in anti-CCP levels have yielded conflicting results. In addition, to our knowledge the correlation between autoantibodies and tocilizumab treatment has been poorly investigated. Objectives: This study investigates the relationship between the presence and levels of RF and anti-CCP and clinical response to tocilizumab in patients with RA. Methods: This was an observational longitudinal study in 27 patients with active, long-standing RA despite previous treatment with >2 DMARDs and/or steroids. Patients were treated with tocilizumab 8 mg/kg every 4 weeks. All patients were assessed using approved clinical scales (VES, PCR, HAQ, DAS28-VES, DAS28-PCR, CDAI, and SDAI). IgM-, IgA- and IgG-RFs and anti-CCP antibodies were assessed using ELISA at baseline, 3 months (T1), 6 months (T2), and 12 months (T3). Results: All patients showed significant and sustained clinical response to tocilizmuab treatment. All clinical scales with the exception of HAQ significantly decreased. There was a significant correlation (p=0.03) between anti-CCP and SDAI changes from baseline at T1 and T2. Likewise there were no significant correlations between antibody count at T0 and changes in the DAS-28 VES at T1 and at T2. No significant relationship between clinical scales and antibody levels RF-IgG, IgA, IgM and anti-CCP levels were observed. Conclusions: Tocilizumab is effective in treating the clinical symptoms of RA, and the efficacy of this molecule was not correlated with either RF or anti-CCP levels. There is now a growing body of evidence suggesting that markers associated with clinical response may not be the same biomarkers that predict risk of further joint damage References: MIKULS TR, O'DELL JR, STONER JA, ET AL: Association of rheumatoid arthritis treatment response and disease duration with declines in serum levels of IgM rheumatoid factor and anti-cyclic citrullinated peptide antibody. Arthritis Rheum 2004; 50: 3776–82. KARSDAL MA, WOODWORTH T, HENRIKSEN K, ET AL: Biochemical markers of ongoing joint damage in rheumatoid arthritis--current and future applications, limitations and opportunities. Arthritis Res Ther 2011; 13: 215 TAKEUCHI T, TANAKA Y, AMANO K, ET AL: Clinical, radiographic and functional effectiveness of tocilizumab for rheumatoid arthritis patients-REACTION 52-week study. Rheumatology 2011; 50: 1908–15. Disclosure of Interest: None Declared